Answer:
x = 4,
y = 1
Explanation:
Let us solve through elimination ~
1. Multiply top equation -2x - y = -9 by -2, adding that product to the bottom equation 5x - 2y = 18:
-2 (-2x - y = -9) ⇒ 4x + 2y = 18
+ 5x - 2y = 18 + 5x - 2y = 18
2. To further express this algebraic process of adding to find x in this case:
4x + 2y = 18 ⇒ 9x = 36 ⇒ x = 4
+ 5x - 2y = 18
3. Now let us substitute this value of x into the top equation 4x + 2y = 18:
4( 4 ) + 2y = 18
4. And solve for y:
16 + 2y = 18 ⇒ 2y = 2 ⇒ y = 1